Evangélicos vão às urnas: participação das igrejas pentecostais no pleito eleitoral de 2004, no município do Cabo Santo Agostinho - PE - Gomes, Ricardo Jorge Silveira (2017)
The purpose of this dissertation is to investigate the political practices of Pentecostal parliamentarians in the 2004 electoral process in the city of Cabo de Santo Agostinho City, Pernambuco, Brazil. We will study the social and political factors that led the Pentecostal evangelical churches to engage in the electoral process. The research started from the assumptions that the main factors that motivate such churches to engage in electoral litigation were the capacity for political influence in the exercise of the functions set forth in the Federal Constitution, as well as a tendency of plurality of positions, evidencing a greater freedom in what concerns the performance in the party political space. The questions that the research sought to answer not only relate to the identification and qualification of subjects, objects of analysis, but also aspects related to their intentions and ways of acting in the attainment of their objectives. In other words, it was tried to answer: who were the members and religious agents that competed for the positions of councilmen, in the city of Cabo de Santo Agostinho, in the Elections of 2004? What were they looking for? And how did each religious institution or candidate organized theirselfs to attract the votes of the faithful? The methodological paths followed were the readings of the specialized bibliography, the documentary research related to the political and religious trajectory of the characters that were successful in the elections, in public offices of the Legislative Power.